RETARDASI MENTAL RINGAN DENGAN EPISODE PSIKOSIS SEBUAH LAPORAN KASUS - I Kadek Agus Setiawan (E-Jurnal Medika Udayana, 2014)
Mental Retardation is the decrease of intellectual function thoroughly which occour in development phase and related with social adaptation disturbance. Whereas psychosis isdisturbance of personality (mental) function in assess reality, relationship, perception,persons perceptive and effective conception to certain standard, so that improbability togetting tasks done satisfyingly. Frequency of mental retardation occur approximately 1-3%in all population in United State. Although low of incident, investigation about mentalretardation is still needful. This report discuss about mental retardation with psychosisepisode at female 18 years old which show an eccentric and austistic. In psychiatryexamination found with general impression patient with unfair appearance, grimace, lessverbal and visual contact with examiner (no attention in anamnesis), autistic, purifyconsciousness, mood/affect inadequate/blunt. In sensorium examination and cognitionfound less concentration and attention with speak poorly and presence encouragementinstingtualy as hypobulia